The impact of social networks on electric pump adoption and irrigation access in Bangladesh's informal water markets - Deepak Varshney; Banerjee, Anurag; Chakraborty, Shreya; Kishore, Avinash; Manikanta Radhakrishna; Mukherji, Aditi (Elsevier, 2024)
This study examines the role of social networks in the adoption of electric pumps and water buyers' access to irrigation water through electric pumps in Bangladesh. Despite government efforts, adoption rates have remained low (2.5%), especially among small and marginal farmers. Using a "networks within sample" approach, we surveyed 1,225 farmers in 60 villages across Rajshahi and Rangpur divisions of Northwest Bangladesh, gathering information on social interactions among the surveyed farmers within each village. Our analysis reveals significant positive network effects: having an electric pump owner in one's social network increases the likelihood of adoption. Network effects on irrigation market access are more pronounced within the same land size class compared to social interactions across different classes. Notably, the impact on water buyers' access to irrigation through electric pumps is less pronounced when small farmers socially interact with large farmer pump owners in their social network than when the situation is reversed.